Perkembangan Hak Pengelolaan atas Tanah Sebelum dan Sesudah Peraturan Pemerintah Nomor 18 Tahun 2021 tentang Hak Pengelolaan, Hak Atas Tanah, Satuan Rumah Susun, dan Pendaftaran Tanah - Seventina Monda Devita (CV Rewang Rencang, 2021)
Agrarian Act is a form of protection in the agrarian sector. Agrarian law is the law that regulates land, both in relation to civil and government matters and the institutions authorized to do so. The number of regulations related to land makes the author interested in writing about the development and differences in arrangements between pre Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration and after the enactment of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration.